Penerapan Metode North West Corner Terhadap Optimasi Meminimumkan Biaya Transportasi Pengantaran Air Galon - Triana Papilaja; Heru Sutejo; Ananda Nayla; Berliana Elphin Asmuruf; Ina Maria Keru Koridama; Christiani Rianto Lahutung (Tamilis Synex: Multidimensional Collaboration, 2026)
The increasing demand for refill drinking water has encouraged water depots to improve the efficiency of their distribution systems in order to reduce operational costs. Depot Air Minum Ummi in Jayapura serves various customer locations, including households, offices, kiosks, and project areas, with varying daily demand levels. This study aims to apply the North West Corner (NWC) method to determine the initial optimal allocation of gallon water deliveries and minimize transportation costs. The research employed a quantitative approach using a transportation optimization model. Data were collected through direct observation and interviews at Depot Air Minum Ummi, including supply capacity, customer demand, transportation costs, and distribution destinations. The North West Corner method was used to allocate shipments from two delivery sources to two destination areas, namely Hamadi and Entrop. The results showed that the initial allocation consisted of 50 gallons delivered by Delivery Agent 1 to Hamadi, 15 gallons delivered by Delivery Agent 2 to Hamadi, and 35 gallons delivered by Delivery Agent 2 to Entrop. Based on this allocation, the total transportation cost was calculated at Rp 6,950. The findings indicate that the North West Corner method can provide a feasible and efficient initial solution for transportation cost minimization. Therefore, the method can be applied as a decision-support tool in planning gallon water distribution, although further optimization methods may be used to obtain a more optimal solution.